Ease of biofilm accumulation, and efficacy of sanitizing treatments in removing the biofilms formed, on coupons made of materials commonly used in blueberry packing environment. (October 2019) - Gazula, Himabindu; Scherm, Harald; Li, Changying; Takeda, Fumi; Wang, Peien; Chen, Jinru
Abstract: Biofilm-forming ability of six two-strain mixtures of fecal coliforms, isolated from six different fresh market blueberry packing lines in Georgia, was assessed at 10 °C for 7 days on coupons made of materials commonly used for fresh market blueberry packing lines, lugs and clamshells. These materials included stainless steel, rubber, polyvinyl chloride, polypropylene, polyurethane, high-density polyethylene and polyethylene terephthalate. Coupons with developed biofilms were treated for 1 min at room temperature with four different sanitizers commonly used by blueberry packers in Georgia, including 5 ppm chlorine dioxide, 3 ppm ozonated water, 200 ppm quaternary ammonium compound or 200 ppm sodium hypochlorite. Residual biofilms on treated coupons were subsequently quantified using the crystal violet binding assay. On average, the amount of biofilm mass was significantly greater ( P  ≤ 0.05) on polypropylene, compared to the other coupons used in the study. Biofilms formed on polyvinyl chloride and rubber coupons were statisically similar ( P  > 0.05), but were significantly lower than those on polypropylene and polyurethane coupons and significantly higher than those on high-density polyethylene, stainless steel and polyethylene terephthalate coupons. Ozonated water had significantly higher efficiency in biofilm removal than the quaternary ammonium compound which had significantly higher efficiency than chlorine dioxide, followed by sodium hypochlorite. On average, significantly more residual biofilm mass was found on rubber coupons after the sanitizing treatments. The amounts of residual biofilms on polypropylene, polyvinyl chloride and high-density polyethylene coupons were statistically similar, but were significantly higher than those on polyurethane and stainless steel coupons. The evaluated sanitizers had different efficacies in biofilm removal. The type of coupon materials used in the study played a significant role in biofilm accumulation and removal. These results emphazise the importance of selecting proper chemical sanitizers (with high efficacies in microbial inactivation and biofilm removal) and surface materials (with low tendency in attracting microbial attachments) for fresh market blueberry packing lines because these decisions may affect the hygiene conditions of fresh market blueberry packing lines as well as the microbial quality of the fruits. Highlights: Biofilm forming ability of fecal coliforms on several surface coupons was observed. Efficacy of selected sanitizers in the control of biofilms was evaluated. Significantly more/less biofilms were formed on polypropylene/stainless steel surface. Ozonated water was most effective and chlorine was least effective in biofilm removal. Rubber surface was more difficult and stainless steel surface was relatively easier to clean.